(untitled) (Journal of the Bangladesh Agricultural University, 2011)
The morphometric, productive and reproductive traits of indigenous cattle at Sylhet district were studied. A wide variety of coat colours among the cattle of the selected areas was observed. Most of them were of roan colour. The body is small, compact and less fleshy. Wither height and hearth girth were 89.03±11.11 and 112.09±16.68 cm, respectively. The average body length was 119.85±16.96 cm and the chest width was 32.48±6.48 cm. The approximate body weight and horn size of the cattle were 162.77±60.99 kg and 3.94±4.05 cm, respectively. The milk production per day was 1.33±0.4 litres, lactation length was 187.94±14.77 days and the dry period was 220.81±15.68 days. Gestation length and calving interval were found to be 299.19±3.82 days and 453.47± 13.181 days, respectively. The mean age at first calving was 44±1.6 months. The productive and reproductive performances of native cattle of Sylhet district. More detailed studies are needed to recommend the morphometric, productive and reproductive performance of cattle in Sylhet district. Keywords: Native cattle; Morphometric; Reproductive; Productive traits DOI: http://dx.doi.org/10.3329/jbau.v9i1.8749 JBAU 2011; 9(1): 85-89